Do not treat ghosts: anti-methicillin-resistant Staphylococcus aureus (MRSA) therapy in osteomyelitis without identified MRSA - Jincy Varughese; Annie Halfman; Matthew Crotty; Julie Alexander; Leigh Hunter; Mark Hupert; Edward Dominguez (Antimicrobial Stewardship & Healthcare Epidemiology)
Abstract